Multicultural and Diversity Management in Higher Education Institutions in the Philippines - Llantos, Elvira (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The multicultural and diversity management (MDM) encompasses acceptance and respect, recognition and valuing of individual differences of the university stakeholders. This study determined the perceptions of the academic managers/ leaders towards multicultural and diversity management in a higher education institutions. This quantitative descriptive research determined the perceptions of 100 purposively selected academic managers/ leaders of selected higher education institutions in the Philippines. The researcher-designed questionnaire was administered online using Google Form. Data were analysed using frequency, percentage distribution, mean, and rank. The majority of the respondents belonged to the age group of 41- 50 years old. The respondents were dominated by males and were single. In terms of highest educational attainment, the majority of the respondents have a master’s degree with 1- 10 years of work experience. The majority of the respondents were Coordinators/Program Chairs who were Regular/Permanent employees. On the basis of the findings of the study, it can be gleaned that the majority of the respondents believed that multiculturalism and diversity management (MDM) in higher education institutions should be integrated with the human resources programs to improve the lenses of equality in the universities and colleges as a workplace. Most of them believe that the MDM program prepares employees for higher diversity in their team, as such; it helps in welcoming recruits with diverse backgrounds into the academic community and promotes a positive organizational culture. Respondents also believed that multicultural and diversity management in Higher Education Institution is one of the best ways that university employees and students can become accustomed to other cultures, nonjudgmental, respectful, and accepting of differences, receptive to different ways of thinking.